Pharmacological Effects of Salvianolic Acid B Against Oxidative Damage - Xiao, Zhun; Liu, Wei; Mu, Yong-ping; Zhang, Hua; Wang, Xiao-ning; Zhao, Chang-qing; Chen, Jia-mei; Liu, Ping (Frontiers in Pharmacology, 2020)
alvianolic acid B (Sal B) is one of the main active ingredients of Salvia miltiorrhiza, with strong antioxidant effects. Recent findings have shown that Sal B has anti-inflammatory, anti-apoptotic, anti-fibrotic effects and can promote stem cell proliferation and differentiation, and has a beneficial effect on cardiovascular and cerebrovascular diseases, aging, and liver fibrosis. Reactive oxygen species (ROS) include oxygen free radicals and oxygen-containing non-free radicals. ROS can regulate cell proliferation, survival, death and differentiation to regulate inflammation, and immunity, while Sal B can scavenge oxygen free radicals by providing hydrogen atoms and reduce the production of oxygen free radicals and oxygen-containing non-radicals by regulating the expression of antioxidant enzymes. The many pharmacological effects of Sal B may be closely related to its elimination and inhibition of ROS generation, and Nrf2/Keap1 may be the core link in its regulation of the expression of antioxidant enzyme to exert its antioxidant effect. What is confusing and interesting is that Sal B exhibits the opposite mechanisms in tumors. To clarify the specific target of Sal B and the correlation between its regulation of oxidative stress and energy metabolism homeostasis will help to further understand its role in different pathological conditions, and provide a scientific basis for its further clinical application and new drug development. Although Sal B has broad prospects in clinical application due to its extensive pharmacological effects, the low bioavailability is a serious obstacle to further improving its efficacy in vivo and promoting clinical application. Therefore, how to improve the availability of Sal B in vivo requires the joint efforts of many interdisciplinary subjects.